Analysing the performance of liquid cooling designs in cylindrical lithium-ion batteries. (January 2021) - Yates, Matthew; Akrami, Mohammad; Javadi, Akbar A.
Highlights: The performance of two liquid cooling designs for lithium-ion battery packs was investigated. The effects of channel number, hole diameter, mass flow rate and inlet locations are investigated. This study shows the maximum temperature difference of the CCHS is significantly less than the MCC. Considering maximum temperature and temperature uniformity, the MCC design provides superior performance to the CCHS. Abstract: The thermal management of batteries for use in electric and hybrid vehicles is vital for safe operation and performance in all climates. Lithium-ion batteries are the focus of the electric vehicle market due to their high power density and life cycle longevity. To investigate the performance of two liquid cooling designs for lithium-ion battery packs, a series of numerical models were created. The effects of channel number, hole diameter, mass flow rate and inlet locations are investigated on a mini channel-cooled cylinder (MCC) and a channel-cooled heat sink (CCHS); those being the two most efficient concepts. The results show that the maximum temperature can be controlled to under 313 K for both designs with mass flow rates over 5E-05 kg/s, and maximum temperature variation can be controlled to less than 3.15 K for both designs. Considering both maximum temperature and temperature uniformity, the MCC design provides superior performance to the CCHS. The maximum temperature of the MCC is less than that of the CCHS but the temperature is less uniform. The MCC is a more complex design and so would incur greater manufacturing costs. But, it increases the efficiency of such systems for the rechargeable battery packs of the electric vehicle industry.